2022
DOI: 10.1038/s41598-022-26842-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of colonization with multidrug-resistant bacteria in communities and hospitals in Kenya

Abstract: We estimated the prevalence of extended-spectrum cephalosporin-resistant Enterobacterales (ESCrE), carbapenem-resistant Enterobacterales (CRE), and methicillin-resistant Staphylococcus aureus (MRSA) in communities and hospitals in Kenya to identify human colonization with multidrug-resistant bacteria. Nasal and fecal specimen were collected from inpatients and community residents in Nairobi (urban) and Siaya (rural) counties. Swabs were plated on chromogenic agar to presumptively identify ESCrE, CRE and MRSA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 34 publications
(43 reference statements)
1
22
0
Order By: Relevance
“…Antibiotic susceptibility testing. All DEC isolates were tested for susceptibility to 17 antibiotics-belonging to 11 antibiotic classes [16]-using the VITEK ® 2 AST-GN71 cards. Interpretation of antibiotic susceptibility results was based on the 2020 Clinical and Laboratory Standards Institute (CLSI) guidelines [17].…”
Section: Methodsmentioning
confidence: 99%
“…Antibiotic susceptibility testing. All DEC isolates were tested for susceptibility to 17 antibiotics-belonging to 11 antibiotic classes [16]-using the VITEK ® 2 AST-GN71 cards. Interpretation of antibiotic susceptibility results was based on the 2020 Clinical and Laboratory Standards Institute (CLSI) guidelines [17].…”
Section: Methodsmentioning
confidence: 99%
“…Alarmingly, carbapenem-resistant Enterobacterales (CRE) and extended-spectrum-lactamase-producing organisms, which are associated with poor clinical outcomes in invasive infections, are increasingly prevalent in Kenya. A recent study found that 7–17% of hospitalized patients had infections caused by these bacteria, with 39% of isolates meeting the “difficult-to-treat resistance” definition [ 15 ]. This situation poses a significant public health challenge requiring urgent attention.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond antibiotic administration, less is known about other factors that could contribute to colonization before or during hospitalization. Earlier work showed that the prevalence of ESCrE and CRE colonization within a regional hospital in Guatemala (67% and 37%, respectively) is relatively high compared with other low- and middle-income countries [20] , [21] , [22] and very high compared with high-income countries [ 23 , 24 ]. This high prevalence offers an opportunity to detect potential contributions from the community to colonization in hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%